FIRE HOT SPOT CHARACTERIZATION AND DETECTION IN THE PANTANAL USING SATELLITE IMAGES - Ribeiro do Valle Goncalves, Renata; Carneiro, João Victor Gomes; Lorenzi, Felipe De (Ra’e Ga: o Espaço Geográfico em Análise, 2025)
The Pantanal, the world’s largest floodplain, is area prone to fire, presenting major impacts on the distribution and survival of fauna and flora species. The recent drought in the Pantanal has been more intense, increasing the occurrence of seasonal fires in the Biome. The objective of this paper is to detect possible fire foci and evaluate the burned areas considering the radiative power of fire in June-July 2020 and in June-July 2024, using images from the GOES-16 meteorological satellite. For the detection and monitoring fire hot spots in real time, the Fire Detection and Characterization (FCDC) product was used, considering the visible and infrared spectral bands. The values ​​of the radiative power of the fire and the burned area of ​​the fire hot spot were extracted to assess the intensity of the fire in the years 2020 and 2024. The selected fire hot spots were only those which presented a high chance of fire. In 2020 the total burned area was ​​582,664 m2 with an average radiative power of 43.41 MW and in 2024 a total burned area of 636,724 m2 and an average radiative power of 56.17 MW. Data from the GOES-16 satellite can monitor the progression and spread of vegetation fires. It helps to guide the decision-making for the implementation of warning systems, providing high-quality information, such as the exact location of the outbreaks and the intensity of a fire.